2018
DOI: 10.1111/ans.14427
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pelvic exenteration service at a tertiary referral centre

Abstract: Our experience confirms that radical resectional pelvic surgery can be safely performed with acceptable results during the establishment phase of a dedicated tertiary service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…There are now four colorectal surgeons involved, approximately 250 referrals per year and 80 resections performed per year. In Brisbane, 61 patients underwent exenteration in approximately 5 years before the study [7].…”
Section: Resultsmentioning
confidence: 99%
“…There are now four colorectal surgeons involved, approximately 250 referrals per year and 80 resections performed per year. In Brisbane, 61 patients underwent exenteration in approximately 5 years before the study [7].…”
Section: Resultsmentioning
confidence: 99%
“…during the establishment phase of a dedicated tertiary service. 5 In their reviewed cases including 34 locally advanced, 25 recurrent pelvic tumours and two non-neoplastic pathologies, there was a 91.5% R0 resection rate, 52.5% overall complication rate, 26.2% rate of Clavien-Dindo IIIb complications, 3.3% 30day mortality and 8% 12 month mortality rate. 5 Traeger et al (Adelaide, 2022) in their cohort of 113 patients (between 2008 and 2021) also demonstrated improvement in outcomes post development of a dedicated pelvic exenteration service, including higher rates of R0 resection (93.9% versus 84.2%) and lower rates of Clavien-Dindo grade IV complications (8.5 versus 31.3%).…”
Section: Discussionmentioning
confidence: 98%
“…These early technical approaches and multidisciplinary collaboration with local surgeons, anaesthetists, oncologists, radiologists, led to early promising results 27 . More recently, these collaborations have led to the development of exenteration centres in Brisbane, 28 Auckland, and Adelaide 29 . This is a testament to collegiality, ensuring early experiences and mistakes are minimized, and training is provided to local exenteration surgeons.…”
Section: Discussionmentioning
confidence: 99%